The prophetic foods consumption among exclusively breastfeeding mothers in Kuantan, Pahang: An exploratory study - Abdul Basir, Siti Munirah; Abdul Ghani, Radiah; Ibrahim, Muhammad; Khattak, Muhammad Muzaffar Ali Khan; Omar, Muhammad Nor; Mohd Shukri, Nor Azwani (IIUM Press, 2018)
The World Health Organization (WHO) and United Nations Children’s Fund (UNICEF) strongly advocate exclusive breastfeeding for the first six months after birth as the optimal way of feeding infants. Nutritional inadequacy during breastfeeding period may lead to breastfeeding problems such as inadequate milk production which is a common reason to early breastfeeding termination. Galactagogue is one of the solutions seek by breastfeeding mothers to overcome this problem. Within the topic of prophetic medicine, scholars discussed the foods consumed by Prophet Muhammad (P.B.U.H) and their health benefits. Among the plants mentioned in Islamic literature are F.carica (figs), O.europea (olive), P.granatum (pomegranate) and N.sativa (habbatussauda). Studies on prophetic foods consumption among lactating mothers is limited in the literature. Thus, the aims of this study to explore on prophetic food consumption, among Malay mothers during exclusive breastfeeding period. Ten subjects are interviewed by in-depth semistructured interview guide. Inclusion criteria include Malay mothers aged 18 to 40 years, deliver full term babies and were exclusively breastfeeding. Audio-recorded interviews were transcribed verbatim in Malay and translated into English. Translated transcripts were then analysed thematically with the help of NVivo software. Thematic analysis revealed three themes that represents participants’ knowledge, attitude and practice on prophetic foods consumption. The themes were 1) prophetic diet is related to Prophet Muhammad (P.B.U.H)’s practice on foods and eating manners, 2) perceived benefits and effectiveness of prophetic foods consumption, and 3) Practice of prophetic foods consumption during exclusive breastfeeding period. This study provides an insight to the understanding and perception on prophetic foods consumption during exclusive breastfeeding period among breastfeeding mothers. It is acknowledged that prophetic foods, particularly dates may have lactogenic function. Further studies should be carried out to investigate the relationship between prophetic foods consumption and lactogenic activity.